Ответ:
дано
m(H2SO4) = 23 g
-----------------------
m(H2O) - ?
3H2SO4+2Fe(OH)3-->Fe2(SO4)3+6H2O
M(H2SO4) = 98 g/mol
n(H2SO4) = m/M = 23 / 98 = 0.23 mol
3n(H2SO4) = 6n(H2O)
n(H2O) = 0.23*6/3 = 0.46 mol
M(H2O) = 18 g/mol
m(H2O) = n*M =0.46* 18 = 8,28 g
ответ 8.28 г
Объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
дано
m(H2SO4) = 23 g
-----------------------
m(H2O) - ?
3H2SO4+2Fe(OH)3-->Fe2(SO4)3+6H2O
M(H2SO4) = 98 g/mol
n(H2SO4) = m/M = 23 / 98 = 0.23 mol
3n(H2SO4) = 6n(H2O)
n(H2O) = 0.23*6/3 = 0.46 mol
M(H2O) = 18 g/mol
m(H2O) = n*M =0.46* 18 = 8,28 g
ответ 8.28 г
Объяснение: